Nasionalisme dalam Teks Keagamaan Indonesia Masa Depan - Choirul Fuad Yusuf (Jurnal Lektur Keagamaan, 2017)
This article aims at: (i) describing condition of Indonesian”s  nationalism, (ii) analysing the socio-political effects  of religious texts toward nationalism in Indonesia, and (iii) proposing strategic alternatives for empowering the future Indonesian’s nationalism. Through an inductive-deductive approach, the article highlights that, unavoidably,  globalization has shaped any condusive situation for the growth and development of universal and transnational ideologies. Globalisation of religious text—liberal, radical, and moderate-- has been capable of breeding transnationalism ideologies in Indonesia. For the sake of stopping the growth of such destructive ideologies, the use of socio-cultural approach is necessarily needed. Which is carried out by (i) controlling and censoring adequatrely toward religious texts, and (ii) revitalilizing the constructive religious text legacies, (iii) intensifying and extensifying committment and responsibility of the Goverment, private institution, and society at large to manage any cultural legacies of Nusantara.Key words: globalization, nationalism, religious texts, transnational ideologies,  sociocuktural approach.Artikel ini bertujuan: (i) menggambarkan kondisi nasionalisme Indonesia, (ii) menganalisis pengaruh teks keagamaan transnasional terhadap nasionalisme Indonesia, dan (iii) mengusulkan strategi penguatan nasionalisme Indonesia melalui pendekatan sosial budaya. Dengan menggunakan pendekatan induktif-deduktif, artikel menggaris-bawahi bahwa globalisasi  berdampak kuat terjadinya pertumbuhan dan perkembangan gerakan transnasional. Globalisasi teks keagamaan—baik teks liberal, teks radikal maupun teks moderat—telah menyuburkan pertumbuhan gerakan transnasional di Indonesia. Untuk itu, pendekatan sosial budaya menjadi salah satu salah satu cara efektif untuk menanghambat perkembangan globalisasi faham transnasional, diantaranya melalui: (i) penyaringan, pengontrolan, dan pengawasan terhadap teks keagamaan (ii) revitalisasi khazanah teks-teks keagamaan yang konstruktif bagi nasionalisme Indonesia & NKRI, dan (iii) intensifikasi dan ekstensifikasi program, serta (iv) penguatan komitmen semua pihak—Pemerintah, Pemerintah Daerah, dan masyarakat.Kata kunci: globalisasi, nasionalisme, teks keagamaan, faham transnasional, pendekatan sosial-budaya.